Use of different types of mineral fertilizers in the production of BRS Amélia Ipomoea potatoes in vertical cultivation - Gonçalves , Lilian Fernanda Sfendrych; Rossa, Uberson Boaretto; Gomes, Erik Nunes; Araujo, Joao Celio De; Ribeiro, Eduardo Augusto Werneck; Farias, Daniel da Rosa; Vischetti, Constantino; Casucci, Cristiano (Revista de Ciências Agroveterinárias, 2023)
Ipomoea batatas, popularly known as sweet potato is considered one of the plants with great economic importance for presenting favorable characteristics for the suppy of calories, vitamins and minerals in human food. Among the genotypes with economic potential, the biofortified cultivar BRS Amélia (Ipomoea batatas) stands out, as it has high nutritional values, rusticity and easy handling. Researches indicate that the absence of fertilization technologies can cause lower productivities of sweet potato, making necessary the use of balanced fertilizations. This study aimed to evaluate the development of the biofortified cultivar BRS Amélia, submitted to the use of different fertilization technologies in a vertical cultivation system. The seedlings received different doses of controlled-release fertilizer: 0.0 (control); 30g; 60g; 90g; 120g and a dose of 40g per planting hole of readily soluble NPK 13-13-28. At 180 days, biometric and production parameters data were collected and submitted to analysis of variance and analysis of regression followed by Tukey test at 5 % for separation of means. The application of the controlled release fertilizer had a positive effect on the production of the studied cultivar, favoring the performance of the plants and promoting a increase especially of height, collar diameter, number of leaves, number of shoots, shoot length and chlorophyll. The application of controlled-release fertilizer had a positive effect on plant performance in height, stem diameter, number of leaves, number of branches, branch length and chlorophyll. For the parameters fresh root biomass and dry root biomass, the use of conventional fertilizer showed better results compared to FLC for the production of sweet potato BRS Amélia in fertile soil in the vertical cultivation system. making necessary the use of balanced fertilizations. This study aimed to evaluate the development of the biofortified cultivar BRS Amélia, submitted to the use of different fertilization technologies in a vertical cultivation system. The seedlings received different doses of controlled-release fertilizer: 0.0 (control); 30g; 60g; 90g; 120g and a dose of 40g per planting hole of readily soluble NPK 13-13-28. At 180 days, biometric and production parameters data were collected and submitted to analysis of variance and analisys of regression followed by Tukey test at 5 % for separation of means. The application of the controlled release fertilizer had a positive effect on the production of the studied cultivar, favoring the performance of the plants and promoting a increase especially of height, collar diameter, number of leaves, number of shoots, shoot length and chlorophyll. The application of controlled-release fertilizer had a positive effect on plant performance in height, stem diameter, number of leaves, number of branches, branch length and chlorophyll. For the parameters fresh root biomass and dry root biomass, the use of conventional fertilizer showed better results compared to FLC for the production of sweet potato BRS Amélia in fertile soil in the vertical cultivation system.